Money or Ideas? A Field Experiment on Constraints to Entrepreneurship in Rural Pakistan - Gine, Xavier; Mansuri, Ghazala (World Bank, Washington, DC, 2014)
This paper identifies the relative importance of human and physical capital for entrepreneurship. A subset of rural microfinance clients were offered eight full time days of business training and the opportunity to participate in a loan lottery of up to Rs. 100,000 (USD 1,700), about seven times the average loan size. The study finds that business training increased business knowledge, reduced business failure, improved business practices and increased household expenditures by about $40 per year. It also improved financial and labor allocation decisions. These effects are concentrated among male clients, however. Women improve business knowledge but show no improvements in other outcomes. A cost-benefit analysis suggests that business training was not cost-effective for the microfinance institution, despite having a positive impact on clients. This may explain why so few microfinance institutions offer training. Access to the larger loan, in contrast, had little effect, indicating that existing loan size limits may already meet the demand for credit for these clients.